Deskripsi Kompetensi Pedagogik Guru Matematika Sebagai Dampak Dari Pelaksanaan Pengembangan Keprofesian Berkelanjutan Dalam Bentuk MGMP Di Kabupaten Takalar - Rahman, Abdul; Rosidah, Rosidah; Fadya, Rara Nur (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This study aims to describe the pedagogical competence of teachers after being given Continuous Professional Development (PKB) treatment in the form of MGMP in Takalar Regency. The type of research used is descriptive qualitative research. There are six research subjects, namely mathematics teachers who are members of the MGMP and have participated in the 2015 UKG which are grouped into three parts based on the order of values: high, medium, low. Data collection techniques in this study are by conducting pedagogical competency tests and interviews. The results showed that: Highly competent teachers have the ability to master six aspects of pedagogic competence. Medium competency teachers have the ability to master five aspects of pedagogic competence. Low competence teachers have the ability to master three aspcets of pedagogic competence. In this study, MGMP has been able to contribute to the improvement of teachers' pedagogical competence. The results of this study are expected to add insight and improve the pedagogic competence of teachers.